Evaluation of the prevalence of MASLD, MASH and liver fibrosis in a Dutch bariatric cohort. - Willy Theel; Willem-Pieter Brouwer; Elisabeth van Rossum; Jan Apers; Susan Ter Borg; Tessa Noordermeer; Manuel Castro Cabezas (PLoS ONE)
Background and aims The prevalence of metabolic dysfunction-associated steatotic liver disease (MASLD) and metabolic dysfunction-associated steatohepatitis (MASH) in bariatric populations has been widely studied but may vary geographically. This study evaluates MASLD/MASH prevalence and the utility of non-invasive tests (NITs) for liver fibrosis in a Dutch bariatric surgery cohort. Methods This single-center cross-sectional diagnostic accuracy study included 220 patients undergoing bariatric surgery. At baseline, 10 NITs were performed. Patients with liver stiffness measurements ≥ 8kPa using vibration-controlled transient elastography underwent a liver biopsy during surgery. Histology was assessed using the nonalcoholic fatty liver disease Activity Score. Diagnostic accuracy of NITs was evaluated against histology using sensitivity, specificity, and area under the receiver operating characteristic (AUROC). MASH was defined as steatosis with lobular inflammation and ballooning, with or without fibrosis. At-risk MASH included fibrosis ≥F2. Results Out of 77 patients (35%) eligible for histological analysis, the findings revealed a MASLD prevalence of 50.6%, MASH prevalence of 5.3%, and at-risk MASH prevalence of 2.6%. Most patients had no fibrosis (67.1%), while others exhibited mild fibrosis (F1: 23.7%, F2: 9.2%). Capped MAF-5 effectively identified fibrosis stage ≥2 (AUROC: 0.809), surpassing FIB-4 (AUROC: 0.645). Both the FAST score and capped MAF-5 demonstrated strong performance in detecting at-risk MASH. Conclusion MASLD/MASH prevalence and advanced fibrosis were lower than expected in this Dutch cohort. Capped MAF-5 demonstrated superior performance for fibrosis detection, while transient elastography and FIB-4 were less reliable. Further studies are needed to optimize NIT selection in bariatric populations.